METHODOLOGY AND RESULTS OF DETERMINATION OF DYNAMIC CHARACTERISTICS OF ANGULAR DISTURBED MOVEMENT OF THE AIRCRAFT - Кривоносенко, О. П.; Савінов, О. М.; Сущенко, О. А. (Proceedings of National Aviation University, 2021)
The methodology of obtaining the dynamic characteristics of the angular perturbed motion of the aircraft in the conditions of real operation is determined. The results of the primary processing of the results of the flight experiment in the form of graphical dependences are given. Analytical approximation was performed and models of spectral and cross-spectral densities and navigation signals were obtained.